Development of Artificial Intelligence-Based Digital Learning Media To Improve The Quality of Civic Literacy of Muhammadiyah Senior High School Students In Purbalingga - Wartono Wartono; Iskandar Iskandar; Irfan Fatkhurohman; Elsa Puji Hapsari; Asmawati Asmawati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to develop an Artificial Intelligence (AI)-based digital learning media to improve students' civic literacy at SMA Muhammadiyah Purbalingga. The development of this media is motivated by the growing digitalization in education, which demands innovative learning tools that are adaptable to technological advances while remaining focused on forming intelligent and virtuous citizens (good and thoughtful citizens). This research employs a Research and Development (R&D) approach using the ADDIE model, which comprises five stages: analysis, design, development, implementation, and evaluation. The focus of this study is on the analysis and development stages to produce a feasible and effective learning media product. The results indicate that integrating Artificial Intelligence (AI) in the learning process has positive impacts, such as increasing efficiency, effectiveness, and accessibility in civic education. Moreover, the use of AI encourages students to think critically, creatively, and adaptively in responding to technological advancements within the context of citizenship education. However, potential adverse effects, including overdependence on technology and reduced critical thinking skills, must be anticipated by instilling digital ethics consistent with Islamic values. Therefore, the development of AI-based digital learning media is expected to serve as an innovative solution for effectively and ethically enhancing students’ civic literacy at SMA Muhammadiyah Purbalingga.